Forms and methods of professional development for biology teachers - Kovalchuck, Vasyl; Kubikova, Kateryna; Alieka, Halyna; Pysmenna, Oleksandra; Filatenko, Tatyana (Edelweiss Applied Science and Technology, 2024)
This article explores various forms and methods of professional development for biology teachers within the modern education system. Given the constant evolution and change in biology, teachers must remain at the forefront of knowledge and pedagogical techniques to ensure quality education for their students. The article discusses different forms of professional development and analyzes the role of educational environments and postgraduate education institutions. The conducted survey highlights the significance of implementing professional development and motivating educators in their professional activities. The conclusions of the article are valuable for both biology teachers and educational institutions planning to develop support and training systems for pedagogical staff in the field of biological education. The authors emphasize that the professional development of biology teachers requires a combination of different methods and an active approach to learning. This is essential for the effective implementation of scientific achievements in the educational process and the provision of quality education in this field.